PERLINDUNGAN HUKUM BAGI ANAK PELAKU TINDAK PIDANA PADA TINGKAT PENYIDIKAN KEPOLISIAN DI KOTA PALOPO - Sri Rahayu Amri (Voice of Midwifery, 2016)
Indonesia is one country that is now entering a new phase, a variety of things that were once not a child's behavior - children, now prevalent in our country. Crime and violations of public life as well as deviant behavior by adults only done when it is now in almost every area we have encountered in the lives of children - children of Indonesia, and we can not deny that many children - children who commit criminal acts.In line with the times, followed by the development of various aspects of life, such as the economy, science and technology and then giving both positive and negative impacts. The positive effect is the creation of a wide range of quality products and technology, openness and ease of information obtained through the mass media, electronic media or through the Internet system that aims to enable people to access the information needed. While the negative impact of the current era of globalization, among others, an increase in value crisis of ethics and morals, a lack of a sense of togetherness in public life, concern for fellow human beings thinning, where it has the potential to grow and improve posture against the law in various forms of life both by adults even done by children - children. Establishment of Law - Law No. 23 of 2002 on Child Protection suggests that the Republic of Indonesia is obliged to ensure the welfare of each - each of its citizens, including the protection of children's rights are a basic human right, but the reality is far desire from what is described in the constitution and laws - laws that apply in the country of Indonesia. In accordance with the Act - Act N0. 11 of 2012 on Juvenile Court expressly pointed out that the investigator who handled the case child should be experienced as an investigator, has an interest, attention, dedication and understanding the problems of children, and no less important is have followed technical training on juvenile justice. In response to these conditions, to note the legal protection of children and juvenile justice systems.This study is a doctrinal and non-doctrinal combines normative research and empirical research using annotations through library research methods and field research method. Keywords : Legal Protection, Criminal acts of child, Police investigation.